Estudo estrutural de duas aldazinas e de uma aminochalcona - (:unkn) unknown (Universidade Estadual de Goiás, 2015)
Chalcones and azines are two distinct classes of organic compounds, but they have in common the fact that are easily obtained by the synthesis route, which exhibit enhanced potential for many technological applications, being different according to the presence of substituents and its structural conformation. Crystallography is a scientific methodology that allows to know the molecular three-dimensional arrangement, bringing important information for Molecular Sciences. In this work, were applied the main stages of crystallographic work on the structural study of the aminochalcone C15H12BrNO2, and azines C20H24N2 and C17H17N3O2. The study were carried out for geometrical parameters and supramolecular arrangement, which includes the intermolecular interactions, through structural data and Hirshfeld surfaces (dnorm, shape index and fingerprint). In the case of aminochalcone, has noted the presence of non-classical hydrogen bonds of types O-H···O and C···O-H, in addition to hydrophobic π-π stacking interactions and C-H···π. For azines, computer calculations were performed using Density Functional Theory (DFT), to geometric properties compared with experimental data through RMSD (in the case of C20H24N2 azine, the crystallographic problems justify the calculations); calculations of thermodynamic parameters ΔE, DH and ΔG; and NBOs analysis for C17H17N3O2 azine, motivated by the presence of non-classical hydrogen bonds C-H···O and π-π stacking interactions that stabilizes dimers, but mainly because an unconventional interaction of type C-H···H-C connecting the dimers along the crystalline arrangement.
Keywords: Aminochalcona; Azinas; Cristalografia; Teoria do funcional de densidade; Superfície de Hirshfeld; Aminochalcone; Azines; Crystallography; Density functional theory; Hirshfeld surface; CIENCIAS EXATAS E DA TERRA::QUIMICA; QUIMICA::FISICO-QUIMICA